Antioxidant activity of extracted green algae silpau (Dyctyosphaeria versluysii) - ENDANG S SRIMARIANA; DAN APITULEY (Nusantara Bioscience, 2019)
Abstract. Srimariana ES, Apituley DAN. 2019. Antioxidant activity of extracted green algae silpau (Dyctyosphaeria versluysii). Nusantara Bioscience 11: 153-156. Silpau (Dictyosphaeria versluysii) is a green algae that is widely available in Southwest Moluccas regency, living on coral reefs and not classified as seasonal plants. Silpau has long been used by local people, generally in the form of processed vegetables or colo-colo (traditional food). Except for its nutritional value, comprehensive information about silpau still unknown. Therefore, this study was carried out to determine its potential as an antioxidant. The phytochemical content of silpau was analyzed according to the standard method. The antioxidant activity of green algae silpau extract was carried out by reducing DPPH (1,1-diphenyl-2-picrylhydrazyl) free radicals. Phytochemical test of silpau revealed that silpau contain terpenoid compounds. The result of the study showed that the IC50 value of methanol extract of silpau was 547.97 ppm, indicated that silpau methanol extract categorized as a weak antioxidant.